Unveiling the values inculcation model among Mathematics teachers in developing country: A conceptual approach - Liman, Mukhtar Alhaji; Ibrahim, Mohd Burhan; Othman, Joharry (IOSR, 2012)
The demand for valued-education particularly science education and mathematics education is increasing in light of the global technological advancement. However, research on the area of values associated with mathematics teaching and learning among mathematics teachers remains in its infancy in Nigeria. This study was conducted to unveil the effectiveness of the mathematical values inculcation model among secondary schools mathematics teachers in Nigeria. A sample of 509 mathematics teachers was drawn from the six states of the North Eastern Region of Nigeria. A self-constructed survey instrument was used to gather the data of the study. The independent variables of the study consist of ideological, attitudinal, sociological, computational and motivational mathematical values. Structural equation modeling technique and confirmatory factor analysis (CFA) were conducted. The findings of the study show that there is a significant covariant relationship among the latent constructs for values inculcation in mathematics teaching and learning. There is also adequate support of the values inculcation model among Nigerian mathematics teachers as the model fits the data.